Analisis Percepatan Pelaksanaan Pekerjaan Pada Proyek Pembangunan Jalan Simpang Petai - Sari Galuh (Majapahit) Kecamatan Rumbio Jaya Kabupaten Kampar - Adipa, Tomi; Trikomara, Rian; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Project management in construction covers both time and cost control. Any delay related to construction work may result in cost escalation of which the contractor of the project should pay. The construction of Simpang Petai – Sari Galuh (Majapahit) road project is having work delay along the way to its completion. The work completion at week 32nd can only be fulfilled at 26,08% from its initial target of 37,35% resultingin the project having a marginal delay of 11,27%. Such delay on project should be treated by accelerating the works on the project on the remaining works. Work acceleration can be done by using overtime work alternative, equipment and worker addition alternative, and shift work system alternative. The analysis conducted focuses on works that are in critical line. From the analysis result, it can be obtained cost addition from each alternative used to accelerate works. Cost addition from the analysis are;Rp.5.221.985.034,25 from overtime work alternative; Rp.14.352.243.801,50 from equipment and worker addition alternative; and Rp.11.001.593.778,46 from shift work system alternative.Keywords : construction delay, construction cost, duration control, overtime work, equipment and worker addition, shift work.